LO063: Adverse events in a pediatric emergency department: a prospective, cohort study. (2nd June 2016) - Plint, A.; Dalgleish, D.; Aglipay, M.; Barrowman, N.; Calder, L.A.
Abstract : Introduction: Data regarding adverse events (AEs) (unintended harm to a patient related to health care provided) among children treated in the emergency department (ED) have not been collected despite identification of the setting and population as high risk. The objective of our study was to estimate the risk and type of AEs, as well as their preventability and severity, for children seen in a pediatric ED.Methods: This prospective cohort study examined outcomes of patients presenting to a paediatric ED. Research assistants (RA) recruited patients < 18 yrs old during 28 randomized 8-hr shifts (over 1 yr). Exclusion criteria included unavailability for follow-up and insurmountable language barrier. RAs collected demographics, medical history, ED course, and systems level data. A RA administered a structured telephone interview to all patients at day 7, 14, and 21 to identify flagged outcomes (such as repeat ED visits, worsening/new symptoms, etc). Admitted patients' health records were screened with a validated trigger tool. A RA created narrative summaries for patients with flagged outcomes/triggers. Three ED physicians independently reviewed summaries to determine if an AE occurred. Primary outcome was the proportion of patients with an AE within 3 weeks of their ED visit.Results: We enrolled 1367 (70.3%) of 1945 eligible patients. Median age was 4.3 yrs (range 2 months-17.95 yrs); 676 (49.5%) were female. Most (n= 1279; 93.9%) were discharged. Top entrance complaints were fever (n=206, 15.1%), cough (n=135, 9.9%), and difficulty breathing (n=108, 7.9%). Eight eighty (6.5%) patients were triaged as CTAS 1 or 2, 689 (50.6%) as CTAS 3, and 585 (42.9%) as CTAS 4 or 5. Only 44 (3.2%) were lost to follow-up. Flagged outcomes/triggers were identified for 498 (36.4%) patients. Thirty three (2.4%) patients suffered at least one AE within 3 weeks of ED visit; 30 (90.9%) AEs were related to ED care. Most AEs (n= 28; 84.8%) were preventable. Management (n=18, 54.5%) and diagnostic issues (n=15, 45.5%) were the most common AE types. The most frequent clinical consequences were need for medical intervention (n=15;45.5%) and another ED visit (n=13, 39.4%). In univariate analysis, age (p=0.005) and weekday presentation (p=0.02) were associated with AEs.Conclusion: We found a lower risk of AEs than that reported among inpatient paediatric and adult ED studies utilizing similar methodology. A high proportion of AEs were preventable.